2002
DOI: 10.1021/bi0120594
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Binding Sites for Both dsRBMs of PKR on Kinase-Activating and Kinase-Inhibiting RNA Ligands

Abstract: The RNA-dependent protein kinase (PKR) is an interferon-induced, RNA-activated enzyme that phosphorylates and inhibits the function of the translation initiation factor eIF-2. PKR has a double-stranded RNA-binding domain (dsRBD) composed of two copies of the dsRNA binding motif (dsRBM). PKR's dsRBD is involved in the regulation of the enzyme as dsRNAs of cellular and viral origins bind to the dsRBD, leading to either activation or inhibition of PKR's kinase activity. In this study, we site-specifically modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 40 publications
3
48
2
Order By: Relevance
“…RNA molecules that bind to the dsRNA-binding motifs (dsRBMs) that constitute the dsRBD of PKR can either function as activators or inhibitors of the protein kinase, depending on the RNA concentration and whether they interact with one or both motifs (Spanggord et al 2002). We therefore investigated whether the HCV IRES possesses either of these activities.…”
Section: Resultsmentioning
confidence: 99%
“…RNA molecules that bind to the dsRNA-binding motifs (dsRBMs) that constitute the dsRBD of PKR can either function as activators or inhibitors of the protein kinase, depending on the RNA concentration and whether they interact with one or both motifs (Spanggord et al 2002). We therefore investigated whether the HCV IRES possesses either of these activities.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, cleavage affinity assays show that binding of PKR to dsRNAs is mediated by either one or both dsRBDs depending on the ligand, and each dsRDB can recognize different sites on the same RNA 5 (a, d, and g) and an anti-ILF3 antibody (b, e, and h). The localization of the nucleus was drawn in panels c, f, and i. molecule (34). In vivo, ADAR1 and ADAR2 mediate site-specific editing of few cellular RNAs, and both enzymes modify the glutamate receptor B subunit transcript but on distinct adenosines (33,35,36).…”
Section: Discussionmentioning
confidence: 99%
“…Manche et al (228) showed that while a duplex sequence of 11 bp could bind to PKR, 33 bp was the minimum length for activation, and maximal activation was achieved with 80 bp. Furthermore, simultaneous binding of PKR to both dsRNA-binding domains is required for its activation (356). This conclusion, however, needs to be tempered by the observation that at least some short dsRNAs can also induce the PKR pathway in a concentration-dependent manner (see below, in the RNAi section).…”
Section: Long Cytoplasmic Dsrnas Trigger Nonspecific and Global Effectsmentioning
confidence: 99%